TINJAUAN TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA (Studi Putusan Nomor 13/Pid.Sus-TPK/2019/PN Mks) - Eka Kusuma Wardani, Dian (Universitas Ekasakti, 2023)
Corruption in the process of procuring goods and services generally occurs due to abuse of authority by state administrators who are involved in the procurement process, from planning to receiving goods and services, by the Budget User (PA) or the Budget User Authority (KPA). This article uses a type of normative research through a case approach, statutory approach Application of the law of material offenses against cases of abuse of authority in cases of corruption in goods and services by the defendant at the Makassar District Court has complied and fulfilled the elements of delict. The judge's aggravating consideration was that the defendant did not support the government's program, which was actively carrying out the prevention and eradication of corruption crimes. and terms of mitigating the sentence against the defendant The defendant was polite in court and frank in giving testimony.